Penyuluhan Hukum Jaminan Kepastian Hukum Kepemilikan Tanah Melalui Pendaftaran Tanah di Kelurahan Nambo - Hasima, Rahman; Heryanti, Heryanti; Zuliarti, Wa Ode; Muchtasar, Rizal; Sarif, Asri; Widyastuti, Endah (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to increase the community's understanding and legal awareness regarding the guarantee of legal certainty of land ownership through land registration in Nambo Village, Nambo District, Kendari City so that it can provide certainty and legal protection for land rights holders. The method of implementing this community service activity is held by the method of legal counseling directly in the form of lectures and questions and answers which are carried out face-to-face with the community. Through socialization and counseling involving various elements of society, this activity is expected to be able to provide a deeper understanding of land registration procedures, proof of land ownership and guarantee of legal certainty of land ownership. In addition, efforts are also made to increase public awareness of the importance of the legality of land ownership to avoid conflicts and legal problems in the future. The results of this activity show that there is an increase in public understanding and awareness of the guarantee of legal certainty of land ownership through land registration in Nambo Village, Nambo District, Kendari City, thus encouraging the community to take care of their land certificates officially to obtain guarantees of legal certainty and legal protection for land rights holders.